2020
DOI: 10.1108/bij-01-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the operational and financial efficiency using a Malmquist data envelopment analysis: a case of Egyptian hospitals

Abstract: PurposeThe efficient use of organizational resources is integral to the existence of prime firms. This study, using Malmquist data envelopment analysis (DEA), aims to assess in the level of operational and financial efficiency and its determinants for ensuring and sustaining excellent performance in 33 Egyptian private hospitals.Design/methodology/approachThis study adopted a Malmquist DEA approach to assess the changes in operational and financial efficiency in Egyptian hospitals. Tobit regression was also us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…DEA has been extensively used by researchers and practitioners to evaluate hospital performance and in measuring the efficiency of various types of healthcare organizations including public hospitals (Alsabah et al, 2020;Ngobeni et al, 2020;Najadat et al, 2020;Kocisova et al, 2018;Almiman, 2018;Mitropoulos et al, 2015;Mogha et al, 2015;Najadat and Alsmadi, 2011;Akazili et al, 2008), university and research hospitals (Akkan et al, 2020;Ilgun and Knoca, 2019;Bahrami et al, 2018;Chowdhury and Zelenyuk, 2016) and private hospitals (Habib and Shahwan, 2020;Gandhi and Sharma, 2018;Mogha et al, 2012). Ngobeni et al (2020) measured the technical efficiency of public hospitals in nine provinces in South Africa based on CRS and VRS-DEA during the period 2017-2018.…”
Section: Operational Efficiency Of Isolation Hospitalsmentioning
confidence: 99%
See 2 more Smart Citations
“…DEA has been extensively used by researchers and practitioners to evaluate hospital performance and in measuring the efficiency of various types of healthcare organizations including public hospitals (Alsabah et al, 2020;Ngobeni et al, 2020;Najadat et al, 2020;Kocisova et al, 2018;Almiman, 2018;Mitropoulos et al, 2015;Mogha et al, 2015;Najadat and Alsmadi, 2011;Akazili et al, 2008), university and research hospitals (Akkan et al, 2020;Ilgun and Knoca, 2019;Bahrami et al, 2018;Chowdhury and Zelenyuk, 2016) and private hospitals (Habib and Shahwan, 2020;Gandhi and Sharma, 2018;Mogha et al, 2012). Ngobeni et al (2020) measured the technical efficiency of public hospitals in nine provinces in South Africa based on CRS and VRS-DEA during the period 2017-2018.…”
Section: Operational Efficiency Of Isolation Hospitalsmentioning
confidence: 99%
“…The results showed that the better equipped and larger departments support the less equipped one, and the interoperability between them must be considered to measure their level of efficiency better. In the same context Habib and Shahwan (2020) used DEA to analyze the operational and financial efficiency of 33 Egyptian private hospitals to identify the most important variables affecting the efficiency of these hospitals. The results confirmed that 17 out of 33 hospitals were found to be inefficient, due to a decrease in their technical efficiency during the analysis period 2014-2016, and that the most important factors affecting both the operational and financial efficiency of these hospitals are the value of health software, operational expenses and the total number of employees.…”
Section: Operational Efficiency Of Isolation Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The control variables can take place as institutional and environmental factors, although they differ according to the purpose of the research (Bobo et al, 2018). Numbers of hospitals, beds, physicians, nurses þ midwives and other health personnel used as inputs in this study were also used as inputs in the studies conducted by Afonso and Aubyn (2011), Mutter et al (2008), Bilsel and Davutyan (2014), Lobo et al (2014), Karagiannis (2015), Samut and Cafri (2016), Chowdury and Zelenyuk (2016), Nistor et al (2017), Guo et al (2017), Du (2018), Guerrini et al (2018), Bobo et al (2018) and Habib and Shahwan (2020). Similarly, it has been observed that the variables of number of outpatients, proportion of inpatients and surgeries and risk-adjusted crude mortality rate are used in most studies in the literature (Mutter et al, 2008;Bilsel and Davutyan, 2014;Lobo et al, 2014;Chowdury and Zelenyuk, 2016;Nistor et al, 2017;Guo et al, 2017;Du, 2018;Bobo et al, 2018;Habib and Shahwan, 2020).…”
Section: Rq1mentioning
confidence: 99%
“…Numbers of hospitals, beds, physicians, nurses þ midwives and other health personnel used as inputs in this study were also used as inputs in the studies conducted by Afonso and Aubyn (2011), Mutter et al (2008), Bilsel and Davutyan (2014), Lobo et al (2014), Karagiannis (2015), Samut and Cafri (2016), Chowdury and Zelenyuk (2016), Nistor et al (2017), Guo et al (2017), Du (2018), Guerrini et al (2018), Bobo et al (2018) and Habib and Shahwan (2020). Similarly, it has been observed that the variables of number of outpatients, proportion of inpatients and surgeries and risk-adjusted crude mortality rate are used in most studies in the literature (Mutter et al, 2008;Bilsel and Davutyan, 2014;Lobo et al, 2014;Chowdury and Zelenyuk, 2016;Nistor et al, 2017;Guo et al, 2017;Du, 2018;Bobo et al, 2018;Habib and Shahwan, 2020). The control variables used in this study (proportion of university graduates, GDP per capita, metropolitan status and population) were found to have an effect on the efficiency score in the studies conducted by Afonso and Aubyn (2011), Bilsel and Davutyan (2014), Karagiannis (2015), Samut and Cafri (2016), Guo et al (2017), Du (2018) and Bobo et al (2018).…”
Section: Rq1mentioning
confidence: 99%